2017
DOI: 10.1111/1462-2920.13774
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes accelerate methane production in pure cultures of methanogens and in a syntrophic coculture

Abstract: Carbon materials have been reported to facilitate direct interspecies electron transfer (DIET) between bacteria and methanogens improving methane production in anaerobic processes. In this work, the effect of increasing concentrations of carbon nanotubes (CNT) on the activity of pure cultures of methanogens and on typical fatty acid-degrading syntrophic methanogenic coculture was evaluated. CNT affected methane production by methanogenic cultures, although acceleration was higher for hydrogenotrophic methanoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
94
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(102 citation statements)
references
References 61 publications
6
94
1
1
Order By: Relevance
“…Since H 2 could not be generated by G. metallireducens , a strict H 2 -utilizer like M. formicicum was rendered incapable of an interspecies association based on H 2 -transfer with this bacterium (Rotaru 2014b). However, more recent studies indicated that conductive carbon nanotubes stimulated methanogenesis by M. formicicum (Salvador et al, 2017). This implied that M. formicicum might be encouraged by the presence of conductive particle to interact syntrophically with Geobacter .…”
Section: Resultsmentioning
confidence: 99%
“…Since H 2 could not be generated by G. metallireducens , a strict H 2 -utilizer like M. formicicum was rendered incapable of an interspecies association based on H 2 -transfer with this bacterium (Rotaru 2014b). However, more recent studies indicated that conductive carbon nanotubes stimulated methanogenesis by M. formicicum (Salvador et al, 2017). This implied that M. formicicum might be encouraged by the presence of conductive particle to interact syntrophically with Geobacter .…”
Section: Resultsmentioning
confidence: 99%
“…In that work, higher concentrations of multiwalled CNT resulted in a growth medium with a more negative ORP, which benefited methanogenesis that ideally occurs at ORP ranging from −200 mV and −400 mV. 118 Nevertheless, Salvador and co-workers 18 also observed that in the absence of a reducing agent, the ORP increased (to values reaching approximately −200 mV), having the opposite effect verified in the assays performed with the reducing agent. Surprisingly, without reducing agent, the methanogenic activity of Methanobacterium formicicum still increased with increasing concentrations of multiwalled CNT.…”
Section: Effect Of Conductive Materials Onmentioning
confidence: 87%
“…In general, lag phases preceding methane production are reduced and methane production rates increase when CM are added to batch experiments. 8,16,[18][19][20]27,74,78,79 In continuous anaerobic digesters, CM also accelerate methane production and contribute for a more stable operation, allowing higher applied organic loading rates while maintaining high COD removal rates. 21,80−83 Only few studies used direct methanogenic substrates, such as acetate or H 2 /CO 2 , 18,24,84,85,98 while most studies used volatile fatty acids, such as butyrate and propionate, and alcohols as substrates to promote the syntrophic metabolism within microbial communities.…”
Section: Effect Of Conductive Materials Onmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recently, several studies revealed that carbon nanotubes successfully promoted methanogenesis in syntrophic co-cultures as well as in complex environmental matrices [79,80]. Li et al [79] explained how the cytotoxicity of carbon nanotubes could be reduced in experiments: in anaerobic condition, the oxidative stress by free radicals is less than in an aerobic environment, and the high-purity (>90% pure) carbon nanotubes used in this study might not induce any significant residual metal toxicity.…”
Section: Other Conductive Materialsmentioning
confidence: 78%